Brand Post Characteristics and Popularity: A Study of Facebook Brand Pages of Food and Beverage Companies - Petrakis, Manolis; Melanthiou, Yioula; Papasolomou, Ioanna; Dekoulou, Paraskevi (My University, 2019)
Social Media, as a tool of information, communication and social interaction plays an important role in marketing, enhancing brand awareness and brand engagement. For this reason, more and more companies publish brand posts and interact with consumers through brand profiles and pages in Social Media. The current research aims to investigate which features of brand posts enhance their popularity, resulting in more ‘liking’, commenting, and sharing, thus provoking online "word-of-mouth" communication. 451 corporate posts were analysed from 9 leading Greek companies in the Food and Beverage sector, during a three (3) month period. The results show that message irritability, interactivity and thematic content cause online reactions of different intensity, revealing in parallel a different grading of commitment to companies and products. Particularly, ‘liking’ is positively influenced by publications with tips about products use and healthy nutrition, contests, corporate news/CSR, videos, advertising messages, festive and anniversary posts, and less with links and images. Additionally, post commenting can be triggered through contests, video / GIF, festive and anniversary posts, corporate news / CSR, images, calls for commenting and links to other SM pages or sites. Finally, post sharing is enhanced by contests, video / GIF, social and leisure activities, photos and links. The findings of this study can guide digital marketers managing brand fan pages to focus on those characteristics or content that trigger e-WOM communication and strengthen engagement of SM users.
Keywords: Social media optimization; Facebook Brand page; Brand post popularity; Consumer Engagement; Like; Comment; Share; Content marketing